2021
DOI: 10.21037/atm-20-8124
|View full text |Cite
|
Sign up to set email alerts
|

Safety of immune checkpoint inhibitors in patients with cancer and pre-existing autoimmune disease

Abstract: Background: Patients with pre-existing autoimmune disease (AD) have been largely excluded from clinical trials of immune checkpoint inhibitors (ICI), so data on safety of ICIs among patients with pre-existing AD are relatively limited. There is a need for deeper understanding of the type and management of complications from ICI in patients with pre-existing AD. We sought to investigate the safety of ICIs in patients with pre-existing ADs as well as factors associated with AD flare.Methods: Consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“…As concerns of preexisting autoimmune disease exacerbation and/or development of new immune-mediated side effects were major, all patients with an autoimmune disease, regardless of the organ, have been excluded from the clinical trials evaluating ICIs. Consequently, the majority of data available so far on the side effects of ICIs in patients already known with autoimmune disease come from case reports and retrospective studies ( Abdel–Wahab et al, 2018 ; Danlos et al, 2018 ; Kahler et al, 2018 ; Cortellini et al, 2019 ; Tison et al, 2019 ; Alexander et al, 2021 ; Hoa et al, 2021 ). In these works, preexisting autoimmune liver diseases are nearly completely absent.…”
Section: Immune Checkpoint Inhibitor-induced Liver Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…As concerns of preexisting autoimmune disease exacerbation and/or development of new immune-mediated side effects were major, all patients with an autoimmune disease, regardless of the organ, have been excluded from the clinical trials evaluating ICIs. Consequently, the majority of data available so far on the side effects of ICIs in patients already known with autoimmune disease come from case reports and retrospective studies ( Abdel–Wahab et al, 2018 ; Danlos et al, 2018 ; Kahler et al, 2018 ; Cortellini et al, 2019 ; Tison et al, 2019 ; Alexander et al, 2021 ; Hoa et al, 2021 ). In these works, preexisting autoimmune liver diseases are nearly completely absent.…”
Section: Immune Checkpoint Inhibitor-induced Liver Toxicitymentioning
confidence: 99%
“…In a global view, data available up to now describe a higher rate of irAEs (up to 75% of the patients) in patients with a past medical history of autoimmune disease ( Abdel-Wahab et al, 2018 ; Danlos et al, 2018 ; Kahler et al, 2018 ; Cortellini et al, 2019 ; Tison et al, 2019 ; Alexander et al, 2021 ; Hoa et al, 2021 ). Both de novo irAEs and exacerbation of the already known autoimmune disease were reported, independent of the degree of activity (active vs. inactive) of the preexisting disease; immunosuppressive drugs were rarely needed, neither ICI discontinuation.…”
Section: Immune Checkpoint Inhibitor-induced Liver Toxicitymentioning
confidence: 99%
“…Patients with pre-existing autoimmune diseases have been excluded from immunotherapy based clinical trials, and pre-existing autoimmune diseases have been identified in a meta-analysis to be a risk factor for irAE incidence. As one may expect, based on several prospective and retrospective studies, there were higher irAEs in those with pre-existing autoimmune diseases compared to those without [48][49][50]. Table 2 includes several studies of patients with pre-existing autoimmune disease who had treatment with ICI.…”
Section: Pre-existing Rheumatologic Diseasementioning
confidence: 99%
“…Pembrolizumab (50), nivolumab A larger systemic meta-analysis characterized irAEs in patients with pre-existing autoimmune diseases. The incidence of pre-existing autoimmune disease flare was 35% and incidence of irAEs was 33%.…”
Section: Pre-existing Rheumatologic Diseasementioning
confidence: 99%
See 1 more Smart Citation